Ideologies of authenticity and progress in jazz criticism - Burke, Patrick (My University, 1999)
Contents include: the 1930s and 1940s - authenticity and notions of the primitive, the 1950s and 1960s - the "new critics" and standards of progress, and African-American critics from the 1960s to the 1990s - authenticity and the black aesthetic.
ii, 88 leaves : 29 cm.